Mn-doped Co2P/N-doped carbon composite materials as efficient bifunctional catalysts for rechargeable Zn-air batteries. (March 2022) - Tong, Jinhui; Wang, Huan; Bo, Lili; Li, Chunyan; Guan, Xiaolin; Kong, Deyuan; Zhang, Yuning; Shi, Wenping; Lei, Zhibin
Highlights: The catalyst is prepared by one-step method. Manganese doping is conducive to improving the electrocatalytic performance. N-doping increases the electrical conductivity and promotes the transmission of electrons. The catalysts exhibit high electrocatalytic activities for OER, ORR and Zn-air battery. Abstract: In this work, several Mn-doped Co2 P/N-doped carbon composite materials were facilely prepared through one-step carbonizing and phosphating treatments. The catalysts have exhibited high bifunctional catalytic activities for OER and ORR. Notably, the optimized catalyst Mn(0.1)-Co2 P/NC exhibited high electrocatalytic activities for ORR (with onset/half-wave potential of 0.856/0.784 V vs. RHE, respectively) and OER (with an overpotential of 370 mV at 10 mA/cm 2 ), which are very near to those of Pt/C (20%) and RuO2 noble catalyst, respectively. When the Mn(0.1)-Co2 P/NC was employed as air electrode catalyst for rechargeable Zn-air battery, the battery exhibited a high open-circuit voltage of 1.351 V, a stable discharge voltage of 1.08 V, a high round-trip efficiency of 47.3% and excellent stability for 100 cycles at 10 mA/cm 2, which is superior to the one using Pt/C (20%) + RuO2 as the air electrode catalyst. Graphical abstract: A series of Mn-doped Co2 P/N-doped carbon composite materials were facilely prepared and used as the air cathode for rechargeable Zn-air battery. The optimized sample Mn(0.1)-Co2 P/NC exhibited highly efficient catalytic activities for OER and ORR. Image, graphical abstract